2011
DOI: 10.3109/00016489.2011.567998
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile tinnitus in perimenopausal period

Abstract: Sigmoid sinus diverticulum-induced pulsatile tinnitus is a rare medical problem. Here we report a case where pulsatile tinnitus occurred in the perimenopause with evidence of sigmoid sinus diverticulum. The tinnitus disappeared with the restoration of hearing after surgery. While diagnosis is critical for the treatment, this disorder can be diagnosed relatively easily, and a satisfactory therapeutic outcome can be achieved using a simple surgical approach. The sigmoid sinus diverticulum may be a clinical manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Three main theories have been proposed for the mechanism of SSDD, the idiopathic intracranial hypertension (IIH) theory [5], blood flow impacting theory [6,3,5], and osteoporosis theory [7]. According to the blood flow impacting theory, SSDD is caused Liu Zhaohui and Dong Cheng contributed equally to this work.…”
Section: Introductionmentioning
confidence: 98%
“…Three main theories have been proposed for the mechanism of SSDD, the idiopathic intracranial hypertension (IIH) theory [5], blood flow impacting theory [6,3,5], and osteoporosis theory [7]. According to the blood flow impacting theory, SSDD is caused Liu Zhaohui and Dong Cheng contributed equally to this work.…”
Section: Introductionmentioning
confidence: 98%
“…One of the venous etiologies of PT is sigmoid sinus diverticulum (SSD). SSD is an outpouching from the sigmoid dural venous sinus that is usually laterally or anteriorly oriented, and is often associated with an upstream transverse or sigmoid sinus stenosis 1,1316 . Altering the flow of venous blood through the SSD and the parent sinus by manual compression of the ipsilateral internal jugular vein (IJV) is known to mitigate symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In assessing risk of bias, 7 studies were assessed as low risk 5,8,14,24-27 and 13 as high risk 4,6,7,9,10,22,28-34 for selective outcome reporting. For incomplete outcome data, 8 studies were assessed as low risk 6-8,14,24-26,33 and 4 as high risk, 4,5,27,30 and 8 studies could not be assessed because they reported only 1 case 9,10,22,28,29,31,32,34 (Supplemental Table S1, available in the online version of the article).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen included studies reported a total of 121 resurfacing cases to treat PT associated with SSWA. Nine studies reported on sigmoid sinus diverticulum, 4,5,7,8,26,27,32-34 and 7 reported on sigmoid sinus dehiscence. 4,8,24-26,28,30 Transmastoid resurfacing approaches were used in all cases ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%